Multicultural Equality and Justice in Education: Implications for Character Education - Ronaldi; Zulpandri; Mahyudin Ritonga; Julhadi; Umar Alhaji Umar (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This article aims to analyze the concept of multicultural equality and justice in education, particularly from the perspective of Islamic education, as well as explain its implications for the formation of character education in a multicultural society. Theoretical framework: This research is based on the theory of multicultural education (Banks and Nieto), the theory of social and distributive justice, and the value of Islamic education that emphasizes al-'adl (justice) and al-musāwah (equality). Literature review: The literature review examines studies on multicultural education, social justice, and Islamic education, and shows that there is still limited research that integrates multicultural equality and justice within the framework of Islamic education. Methods: The research uses a qualitative approach through a literature study of books, journal articles, and education policy documents, with content analysis and conceptual synthesis. Results: The results of the study show that equality in Islamic education is interpreted as recognition of equal human dignity, while justice is understood as the provision of rights and opportunities for learning proportionally. The integration of these two principles in multicultural education contributes significantly to the formation of the character of students who are tolerant, fair, and responsible. Implications: Theoretically, this study enriches the study of Islamic-based multicultural education; practically, it becomes the basis for the development of an equity- and justice-oriented curriculum, learning, and school culture. Novelty: The novelty of the research lies in the systematic integration of the concept of multicultural equality and justice with character education from the perspective of Islamic education.